MINIATUR SISTEM TRANSFER FLEKSIBEL DENGAN PENGENDALIAN TERDISTRIBUSI MENGGUNAKAN PLC - Yatna Yuwana Martawirya; Akhmad Hery Kusuma; Yohanes Kurnia Pamungkas (Mesin, 2002)
The objective of the present research is to develop a miniature of a module of the Flexible Transfer System (STF). STF is the alternative solution of system transportation in advance manufacturing system environment which considered ï¬‚exible on its components. The ï¬‚exibility that can be fulfilled by STF is the ï¬‚exibility in a route of transportation and the ability to be developed in the future. For these purposes, the control architecture of STF is designed to be distributed and each of the controllers has autonomy to carry out decision making based on its condition. At this research a miniature of STF that consists of a mechanical system module, an executor controller, and a manager controller has been developed, and the communication among the distributed controllers has been carried out and successfully.